2018
DOI: 10.1111/petr.13274
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated histoplasmosis in pediatric kidney transplant recipients—A report of six cases and review of the literature

Abstract: KTx patients in endemic areas are at risk for disseminated histoplasmosis. Further study is needed to determine which factors portend the need for fungal prophylaxis in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…We thus present a case of disseminated histoplasmosis in a kidney transplant patient. While there have been previous reports of this in the literature, our case is unique in our patient's underlying genetic condition, travel history, and diagnosis with no known clear exposure to Histoplasma endemic areas (2,15). With the use of novel diagnostic techniques including Karius, serum metagenomics, and nextgeneration sequencing, we were eventually able to identify histoplasmosis, a feat that would have been difficult with cultures alone (16).…”
Section: Discussionmentioning
confidence: 72%
“…We thus present a case of disseminated histoplasmosis in a kidney transplant patient. While there have been previous reports of this in the literature, our case is unique in our patient's underlying genetic condition, travel history, and diagnosis with no known clear exposure to Histoplasma endemic areas (2,15). With the use of novel diagnostic techniques including Karius, serum metagenomics, and nextgeneration sequencing, we were eventually able to identify histoplasmosis, a feat that would have been difficult with cultures alone (16).…”
Section: Discussionmentioning
confidence: 72%
“…While viral infections are far commoner in solid organ transplant recipients, fungal infections are usually more serious [ 50 ]. Studies have reported on occurrences of disseminated histoplasmosis in pediatric kidney transplant patients which are by far the commonest solid organ transplants done in the pediatric age group [ 92 , 94 ]. Hemophagocytic lymphohistiocytosis has often been reported in association with histoplasmosis infection in kidney transplant recipients and this complicates the management and often worsens the prognosis [ 50 , 92 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported on occurrences of disseminated histoplasmosis in pediatric kidney transplant patients which are by far the commonest solid organ transplants done in the pediatric age group [ 92 , 94 ]. Hemophagocytic lymphohistiocytosis has often been reported in association with histoplasmosis infection in kidney transplant recipients and this complicates the management and often worsens the prognosis [ 50 , 92 , 94 ]. A case series of six pediatric kidney transplant patients in an endemic region of the USA put the attack rate of histoplasmosis among kidney transplant patients at 6.9/100 cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations